1998
DOI: 10.1074/jbc.273.42.27051
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Protein Containing cdc10/SWI6 Motifs Regulates Expression of mRNA Encoding Catecholamine Biosynthesizing Enzymes

Abstract: Catecholaminergic (dopaminergic, noradrenergic, and adrenergic) transmitter phenotypes require the cooperative actions of four biosynthetic enzymes: tyrosine hydroxylase, aromatic L-amino acid decarboxylase, dopamine ␤-hydroxylase, and phenylethanolamine N-methyltransferase. Mechanisms that control expression of these enzymes in a transmitter phenotype-specific manner, however, are poorly understood. Here, we provide evidence that overexpression of a novel cdc10/ SWI6 motif-containing protein, V-1, elicits the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
37
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 43 publications
9
37
0
Order By: Relevance
“…Myo/V1 is a 12-kDa ankyrin repeat-containing intracellular protein that has been found at elevated levels in failing human hearts (5) as well as in the hearts of spontaneously hypertensive rats (6). Although Myo/V1 was originally described as a trophic protein (myotrophin) exhibiting growth properties exogenously on rat neonatal myocytes (1), other studies showed that this protein was only present in intracellular space (2,(7)(8)(9) and its trophic growth properties on neonatal myocytes were not confirmed (10). Moreover, this protein was originally identified and isolated only from an intracellular location (1), and a transcriptional regulatory function has been proposed (3,9).…”
mentioning
confidence: 99%
“…Myo/V1 is a 12-kDa ankyrin repeat-containing intracellular protein that has been found at elevated levels in failing human hearts (5) as well as in the hearts of spontaneously hypertensive rats (6). Although Myo/V1 was originally described as a trophic protein (myotrophin) exhibiting growth properties exogenously on rat neonatal myocytes (1), other studies showed that this protein was only present in intracellular space (2,(7)(8)(9) and its trophic growth properties on neonatal myocytes were not confirmed (10). Moreover, this protein was originally identified and isolated only from an intracellular location (1), and a transcriptional regulatory function has been proposed (3,9).…”
mentioning
confidence: 99%
“…Previous studies suggested the potential role of V-1 in the signal transduction pathways leading to catecholamine synthesis or to cardiac hypertrophy. For example, Yamakuni et al (5)(6)(7) demonstrate that the overexpression of V-1 caused a significant increase in the catecholamine level in PC12 cells, presumably through the transcriptional activation of the genes for catecholamine synthesis. In other reports (8 -11), V-1 was designated as "myotrophin" and was shown to participate in the cell signaling pathways for the NFkB-mediated activation of protein synthesis in the myocytes.…”
mentioning
confidence: 99%
“…V-1 is important for expression of catecholamine-synthesizing enzymes (7), differentiation and regeneration of skeletal muscle (8), folliculogenesis and corpus luteum formation in the ovary (9), and regulation of insulin secretion (10). We will refer to the myotrophin/V-1 protein as V-1 for simplicity.…”
mentioning
confidence: 99%